The Mobility of Myanmar Labours in the Fish ery Industryin Muang District, Ranong Province - พิศการณ์, วารุณี; ถาวรประสิทธิ์, บุษกร (Parichart Journal, 2017)
This research aims to study the characteristics, the factors affecting cost and length of mobility, and the level of problems of the migration of Myanmar labors in the fishery industry in Muang district, Ranong province. The data were collected from 400 samples. The study employed frequency, percentage, standard deviation, and Multiple Regression for analysis. The study found that most have moved by agent, the average cost for moving was 14,290.75 baht and the average length of the trip was 5.37 days, and the reason of mobility was the high wage rate in Thailand compare with Myanmar. The factors that influence cost and length of mobility were education, birthplace, family members, debt, occupation and experience in Myanmar significantly at 0.05. Finally, the level of problems was 3.21 that was at a moderate level.